Estudio de viabilidad para la obtención de combustible sintético a partir del gas de quema producido en Campo Orito, Putumayo. (2022)
Important parts in the acquisition of goods and services for a nation, however, during its operation is realized a deliberate release of associated gas process, this gas is mostly obtained from the oil extraction and tons of methane and CO2 emissions are released directly to the atmosphere, being these the protagonists of greenhouse gases (GHG), in addition to other emissions that recharge the environment with toxic substances such as soot (black carbon).